Case report: A novel frameshift mutation in BRSK2 causes autism in a 16-year old Chinese boy - Hu, Yu; Li, Miao; Shen, Yanmei; Wang, Tianyun; Liu, Qiwei; Lu, Zhonghua; Wang, Hong; Luo, Xuerong; Yang, Lixin (Frontiers in Psychiatry, 2023)
Serine/threonine protein kinases are involved in axon formation and neuronal polarization and have recently been implicated in autism spectrum disorder (ASD) and neurodevelopmental disorders (NDD). Here, we focus on BRSK2, which encodes brain-specific serine/threonine protein kinase 2. Although previous studies have reported 19 unrelated patients with BRSK2 pathogenic variation, only 15 of 19 patients have detailed clinical data. Therefore, more case reports are needed to enrich the phenotype associated with BRSK2 mutations. In this study, we report a novel de novo frameshift variant (c.442del, p.L148Cfs*39) identified by exome sequencing in a 16 year-old Chinese boy with ASD. The proband presented with attention-deficit, auditory hallucinations, limb tremor, and abnormal brain electrical activity mapping. This study expands the phenotypic spectrum of BRSK2-related cases and reveals the highly variable severity of disorders associated with BRSK2.